2020
DOI: 10.1002/we.2481
|View full text |Cite
|
Sign up to set email alerts
|

A simple improvement of a tip loss model for actuator disc simulations

Abstract: The loading of a wind turbine decreases towards the blade tip because of the velocities induced by the tip vortex. This tip loss effect has to be taken into account when performing actuator disc simulations, where the single blades of the turbine are not modeled. A widely used method applies a factor on the axial and tangential loading of the turbine. This factor decreases when approaching the blade tip. It has been shown that the factor should be different for the axial and tangential loading of the turbine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Of the LES and RANS models, again only LES DTU predicts a decay of F t . The other models show a typical bump that originates from the spurious induction of the trailing tip vortex [77] (or the vortex sheet for the ADM in RANS UU , respectively [91]). When compared to Case A, DWM DTU is in closer agreement with most of the LES models.…”
Section: Power and Loads Of The Downstream Turbinementioning
confidence: 99%
“…Of the LES and RANS models, again only LES DTU predicts a decay of F t . The other models show a typical bump that originates from the spurious induction of the trailing tip vortex [77] (or the vortex sheet for the ADM in RANS UU , respectively [91]). When compared to Case A, DWM DTU is in closer agreement with most of the LES models.…”
Section: Power and Loads Of The Downstream Turbinementioning
confidence: 99%
“…The factor multiplying p in Equation ( 18) is identical to i w,b for a vortex of constant radius, t = 1, at the "equivalent pitch" of p * = p 2 + k 2 * . This changes the equation for F w from Equation (6) to…”
Section: Resultsmentioning
confidence: 99%
“…Modifications to Prandtl's formulation have been developed by a number of authors, including Shen et al [5]. A more recent example of this type of analysis is by [6]. None of these modificatons address the effects of wake expansion.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, provided that the profile drag remains essentially constant in the considered region of the wing, and that the lift coefficient is corrected to match the reference results, then the error on the drag distribution necessarily originates from a misprediction of the downwash. As also shown by Pirrung et al (2020), it is therefore preferable to correct the effective angle of attack to obtain the correct drag, while also maintaining a correct value for the lift. This is possible due to the small value of the downwash angle.…”
Section: Correction Function For the Angle Of Attackmentioning
confidence: 99%
“…This correction was then extended by Wimshurst & Willden (2017) by comparing ALM to blade-resolved simulations and deriving separate correction functions for the normal and tangential loads. Pirrung et al (2020) then showed that applying the Shen correction to the angle of attack led to an improved accuracy of the normal and tangential loads. Sørensen et al (2016) also developed a decambering correction to take into account the variation of the induced velocity on the blade surface when using a lifting line approach.…”
Section: Introductionmentioning
confidence: 99%